2008
DOI: 10.1080/07325220802487915
|View full text |Cite
|
Sign up to set email alerts
|

How Does Clinical Supervision Work? Using a “Best Evidence Synthesis” Approach to Construct a Basic Model of Supervision

Abstract: Clinical supervision is of growing importance, but poor conceptualization continues to impede research and practice. We conducted a ''best evidence synthesis'' (empirical review) of the literature to generate an integrative summary of the concepts and models used (implicitly or explicitly) in 24 published empirical articles. Using the qualitative data from these adequately rigorous, successful manipulations of supervision, we constructed inductively a basic model of clinical supervision. That is, we proffer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 60 publications
2
124
1
7
Order By: Relevance
“…This would require the testing of logic models based on theoretical development which link organisational context and the provision of a clearly defined model of supervision to direct practice and consumer outcomes. Milne et al (2008) present one approach to understanding how supervision 'works' based on a review of evidence mainly from residential services for people with intellectual disability. The review is very useful in identifying contextual and process variables leading to outcomes for practitioners, however, their model stops short of outcomes for consumers.…”
Section: Discussionmentioning
confidence: 99%
“…This would require the testing of logic models based on theoretical development which link organisational context and the provision of a clearly defined model of supervision to direct practice and consumer outcomes. Milne et al (2008) present one approach to understanding how supervision 'works' based on a review of evidence mainly from residential services for people with intellectual disability. The review is very useful in identifying contextual and process variables leading to outcomes for practitioners, however, their model stops short of outcomes for consumers.…”
Section: Discussionmentioning
confidence: 99%
“…There is however limited empirical research into the nature and effectiveness of supervisory practice in social work (Bruce and Austin 2001). Milne (2008) reviewed the empirical research publications and, using the best evidence synthesis method, identified only 24 peer-reviewed articles on the impact of supervision. Yoo (2005) found only 34 research reports between 1950, and Bogo and McKnight (2005 found 22 studies, mostly small-scale, between1994 and 2004, half of which were published outside the USA.…”
Section: Professional Supervisionmentioning
confidence: 99%
“…This was unexpected, because following training and feedback, observation was the third most common approach to CS found in a systematic review. 27 It has also been reported that the supervisory relationship with less-experienced staff tends to be more directive and is more likely to include observation of practice, but that supervision of more experienced therapists is described as collegial and cooperative, 28 with less emphasis on observation. We suggest that further study is needed to determine the role of observation of practice in CS, including consideration of the level of experience of the supervisee.…”
Section: Content Of Clinical Supervisionmentioning
confidence: 99%